Strengthening the Role of Corporate Social Responsibility (CSR) as a Business Law Instrument in Addressing Flood Impacts in Sumatra - Dita Kartika Sari Hasibuan; Rika Githamala Ginting; Gatot Teguh Arifyanto; Bakhir Mukhammad; Syahrial Arif Hutagalung; Fauzan Ghafur (Ali Institute of Research and Publication, 2026)
The massive floods in Sumatra in 2025–2026 resulted in significant loss of life and economic damage, driven by a combination of extreme weather and environmental degradation linked to business activities. This situation underscores that disaster management is not solely the responsibility of government, but also of the private sector. In Indonesian business law, Corporate Social Responsibility (CSR) constitutes a legal obligation for companies to address the social and environmental impacts of their operations. Therefore, strengthening CSR is crucial as an instrument for sustainable flood mitigation and recovery. This study aims to analyze the role and position of CSR in flood management in Sumatra, to reinforce CSR policies so they contribute more effectively to prevention and mitigation, and to examine corporate accountability when CSR is not optimally implemented, leading to environmental damage and increased flood risk. This research adopts a normative legal method with a descriptive-analytical approach, using statutory and case-based analysis. The data consist of secondary sources, including primary, secondary, and tertiary legal materials, collected through literature and document review and analyzed qualitatively. CSR in flood management functions as a strategic legal instrument for environmental prevention and recovery. Its optimization is essential to strengthen environmental protection and the resilience of flood-prone areas. CSR must shift from a charitable approach to a risk- and sustainability-based framework integrated with environmental and disaster law. Stronger ESG regulation, oversight, and reporting are necessary. Corporate accountability for suboptimal CSR includes administrative, civil, and criminal sanctions, alongside governance and reputational consequences, grounded in precautionary and polluter-pays principles.